A History of the Mishnaic Law of Agriculture: Kilayim : Translation and Exegesis - Mandelbaum, Irving (Book collections on Project MUSE., 2020)
"This volume presents a translation and exegesis of Mishnah's Tractate Kilayim (Mixed Species) in an effort to discover the original meaning of the tractate. This volume aims to identify the sense which the formulators of the tractate's laws wished their rules to convey "--